Transmission electron microscopy study of strain-induced low- and high-angle boundary development in equal-channel angular-pressed commercially pure aluminum - Cabibbo, M.; Blum, Wolfgang; Evangelista, E.; Kassner, M. E.; Meyers, M. A. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2008)
The evolution of the microstructure in a commercially pure aluminum during equal channel angular pressing (ECAP) using route BC was investigated by transmission electron microscopy. Subgrains, or cells, form, which have both high (φ > 15 deg) and low (φ < 15 deg) misorientation. Misorientations and spacings of cell boundaries were determined from about 250 boundaries per pass of ECAP cell boundaries on the basis of Kikuchi patterns and Moiré fringes. The average cell size and misorientation saturate within the first two passes. Misorientations and spacings of high-angle boundaries decrease with the number of passes. After eight passes, the cell size is ≈1.3 μm and the fraction of high-angle boundaries is ≈0.7. The marked differences in the rate of grain structure evolution per pass are linked to differences in the ability of dislocations introduced in new passes to recombine with the existing ones. With increasing ECAP strain, the distribution of misorientations develops strong deviations from the MacKenzie distribution for statistical grain orientation. This is interpreted as a result of the tendency to form equiaxed grains in a textured grain structure. © The Minerals, Metals & Materials Society and ASM International 2007.
Created from Fastlane, Scopus look-up